Reading comprehension processes and strategies in L1 and L2 in Malaysian primary and secondary schools - Sheikh-Ahmad, Ismail (1997)
This study is set in the context of the acknowledged debate, highlighted by the work of Lunzer and Gardner's Schools Council project (1979), concerning the theoretical issue of whether reading comprehension is a unitary competence or consists of identifiable discrete subskills. This long- standing polarised theoretical debate can be traced as far back as the sixties and seventies in the position taken by reading experts such as Spache and Spache (1969), Davis (1971) and Thorndike (1973). Spache and Spache and Thorndike concluded that reading comprehension was a unitary competence, not consisting of separate skills that can be practised in isolation. On the other hand, Davis viewed reading comprehension as composed of separate identifiable skills and abilities. The polarised arguments pose a question as to the nature of reading comprehension. Is there such a thing as discrete reading comprehension sub-skills that can be built up hierarchically and can promote the understanding of texts? With the question in mind this study set out to test whether reading comprehension is a unitary competence of sub-skills or one that can be broken down into separate sub-skills. The research involved the rigorous testing of a series of reading comprehension tests in two languages using four texts taken from the work of Lunzer and Gardner (1979). The texts were modified to suit the socio-cultural context of the students. All of the chosen texts were translated into Bahasa (L1) which is the mother-tongue of the students. In principle, the focus of the study in Part I is centred on replicating the work of Lunzer and Gardner (1979) in some selected Malaysian primary and secondary schools. It seeks to understand whether the main hypothesis holds that reading comprehension is unitary in nature and cannot be broken down into a number of distinct subskills. A selected 300 primary school pupils aged 12 were required to read and answer four comprehension tests written in L1. Another selected 150 secondary school students aged 15 were required to perform the same tasks on material written in L2. Each test has about 30 comprehension questions which are divided into eight categories of subskills. The two groups produced a total of 1,636 valid comprehension tests which were marked rigorously. Factor analysing the data yielded a number of important findings concerning whether reading comprehension subskills are unitary or hierarchic in nature. These findings may suggest some recommendations for improving reading for learning across the Malaysian primary and secondary schools curriculum. In Part I the outlined five chapters discuss the background information which led to the testing of the 450 students, the related literature review, the chosen research design and analysis, the findings and the research implications for the Part II study. The study reported in Part II is an extension of the work done in Part I, in that the remaining five chapters explore the justification of conducting the indepth interviews, the review of the related literature, the design of the interview, the findings and the educational implications of the study. This part explores the reading comprehension strategies that were used by the students in answering the comprehension questions. The second study was successfully made during the summer of 1994. A total of 16 students aged 15 were selected from several secondary schools in Johor Bahru, the capital state of Johor, Malaysia … … The thesis ends with a discussion of the implications from both studies especially for the reading curriculum, instruction, pedagogy, classroom practice and future research.